DHA Accumulation in the Polar Lipids of the Euryhaline Copepod Pseudodiaptomus inopinus and Its Transfer to Red Sea Bream Pagrus major Larvae - Matsui, Hideaki; Sasaki, Taku; Kobari, Toru; Waqalevu, Viliame; Kikuchi, Kazuma; Ishikawa, Manabu; Kotani, Tomonari (Frontiers in Marine Science, 2021)
The euryhaline copepod Pseudodiaptomus inopinus play important roles in coastal waters as vectors of docosahexanoic (DHA) and eicosapentaenoic (EPA) acids for larval fish. While DHA and EPA in polar lipids (PLs) are more effective for fish larval development than non-polar lipid forms (NLs), there is little knowledge how much these lipids are accumulated in copepods from microalgae and are effective for early development of fish larvae. We report PLs fatty acid profiles of P. inopinus fed DHA-poor microalgae and evaluate its significance as a food source for larvae development of Pagrus major, compared with DHA-enriched rotifers. Copepods and rotifers were fed a mixed diet of three algal species (Tisochrysis lutea, Pavlova lutheri, and Phaeodactylum tricornutum), in addition of DHA-supplemented Super Fresh Chlorella (SFC) for rotifers. Compared with SFC, the algal mixture had higher EPA but lower DHA. Copepods had higher DHA and EPA in total lipids than rotifers fed each diet. Copepod PLs were specifically enriched with DHA and their contents were higher than both rotifers. On the other hand, PLs EPA contents were comparable between preys, indicating that copepods selectively fortified the PLs. Fish culture experiment showed that larvae fed copepods had higher growth than those fed SFC-enriched rotifers. Principal component analysis for each organism fatty acid composition emphasized trophic modification of DHA by copepods towards larval fish. This study highlighted that P. inopinus contribute to enhanced growth of coastal larval fish by efficiently transferring DHA via copepod fatty acid metabolism.